Loss of Rbfox1 Does Not Affect Survival of Retinal Ganglion Cells Injured by Optic Nerve Crush - Gu, Lei; Kwong, Jacky M.; Caprioli, Joseph; Piri, Natik (Frontiers in Neuroscience, 2021)
Rbfox1 is a multifunctional RNA binding protein that regulates alternative splicing, transcription, mRNA stability and translation. Its roles in neurogenesis and neuronal functions are well established. Recent studies also implicate Rbfox1 in the regulation of gene networks that support cell survival during stress. We have earlier characterized the expression of Rbfox1 in amacrine and retinal ganglion cells (RGCs) and showed that deletion of Rbfox1 in adult animals results in depth perception deficiency. The current study investigates the effect of Rbfox1 downregulation on survival of RGCs injured by optic neve crush (ONC). Seven days after ONC, animals sustained severe degeneration of RGC axons in the optic nerve and significant loss of RGC somas. Semi-quantitative grading of optic nerve damage in control + ONC, control + tamoxifen + ONC, and Rbfox1-/- + ONC groups ranged from 4.6 to 4.8 on a scale of 1 (normal; no degenerated axons were noted) to 5 (total degeneration; all axons showed degenerated organelles, axonal content, and myelin sheath), indicating a severe degeneration. Among these three ONC groups, no statistical significance was observed when any two groups were compared. The number of RGC somas were quantitatively analyzed in superior, inferior, nasal and temporal retinal quadrants at 0.5, 1 and 1.5 mm from the center of the optic disc. The average RGC densities (cells/mm2) were: control 6438 ± 1203; control + ONC 2779 ± 573; control + tamoxifen 6163 ± 861; control + tamoxifen + ONC 2573 ± 555; Rbfox1-/- 6437 ± 893 and Rbfox1-/- + ONC 2537 ± 526. The RGC loss in control + ONC, control + tamoxifen + ONC and Rbfox1-/- + ONC was 57% (P=1.44954E-42), 58% (P=1.37543E-57) and 61% (P=5.552E-59) compared to RGC numbers in the relevant uninjured groups, respectively. No statistically significant difference was observed between any two groups of uninjured animals or between any two ONC groups. Our data indicate that Rbfox1-mediated pathways have no effect on survival of RGCs injured by ONC.